PEMBARUAN PONDOK PESANTREN SALAF MENUJU MODERN (Studi Tentang Pondok Pesantren Mu’allimat Muhammadiyah Yogyakarta dan al Fathimiyah Bahrul Ulum Tambakberas Jombang Tahun 2014-2015) - Dewi Urifah (LUGATUNA: Jurnal Prodi PBA, 2022)
This thesis aims to determine the continuity and changes in tradition Boarding Mu'allimat Muhammadiyah Yogyakarta and al Fathimiyyah Tambakberas Bahr Ulum Jombang in doing updates from Salaf towards modern. Supporting factors and obstacles in reforming boarding school Muallimat and al Fathimiyyah. This type of research is qualitative with phenomenological approach. Source of data obtained by the primary and secondary data sources. The collection of data through observation, interviews, and documentation. Data analysis technique by reducing the data, display data and draw conclusions. The results showed that the goal of education Boarding Mu'allimat Yogyakarta accordance with the vision and mission boarding school Mu'allimat National Education Goals coupled with the objective of Muhammadiyah and al Fathimiyyah Jombang in accordance with the vision and mission boarding school Mu'allimat National Education Goals, Mu Pesantren Education System Mu’allimat Muhammadiyah Yogyakarta and al Fathimiyyah use madrasa system and Boarding School, Boarding School Education Curriculum Mu'allimat Yogyakarta using integrated curriculum between curriculum KTSP, Boarding plus curriculum Muhammadiyah and al Fathimiyyah Jombang using integrated curriculum between curriculum SBC, boarding school and the Local Content Curriculum relevant. Methodology Education in Yogyakarta and al Fathimiyyah Mu'allimat Jombang, use the same method of Pesantren and conventional and modern methods based student centered. Supporting factors Updates in Pesantren Mu'allimat Yogyakarta; Skills and Expertise Teacher. Skills and Expertise Caregiver Boarding Infrastructures factor, Factor Teacher Education. Fajktor inhibitors: The level of intelligence of students, Student Awareness; Educators are less motivated. Supporting factors Pesantren Al Fathimiyyah: Caregiver Skills, Skills Ustadz, Santri competent, Infrastructures, Environment and Society Early Motivasil. Obstacles include: Pupils are less profesionalis, and the Governing Pupils contemporaries.